Intellectuals when the Aghlabids during the days of the Abbasids (Asad bin Furat and Sahnoun bin Saeed as a model) - AL -swaledl, AbduLzahra oudahluall (International Journal of Psychosocial Rehabilitation, 2020)
The era of the Aghlabids era in Africa is considered one of the most prosperous times of this country in the scientific and cultural field, as it gave birth to a group of scholars, jurists, and poets whose reputation became famous, and their impact spread; and for this it seems that the Aghlabids were likened to the Abbasids, especially with regard to creating public institutions in the cultural state of them, and scientific. Including the library (House of Wisdom), which is similar to what was prevalent in Baghdad during the reign of the Abbasid caliph al-Mamun. The study concluded that Asad Ibn Al Furat, one of the most famous scholars in that country, worked hard to seek knowledge and travel to the provinces in his time to receive the knowledge and take it from the jurists, so he stayed in Medina, Mecca, Baghdad, Kufa, and Egypt. The Battle of Sicily. Imam Sahnoun bin Said Al-Tnoukhi is considered one of the North African scholars, and he appeared in the sciences of jurisprudence, hadith, fatwa and the judiciary.